Neuroprotective Effects of Vitexin and Cajanus cajan Extract Against Pb-induced Neurotoxicity in Wistar Rats - Nathaniel Ohiemi Amedu; Michael Olim Obu (Mazandaran University of Medical Sciences, 2022)
Background: The effects of Pb-induced neurotoxicity have been largely established; however, the need for proper neuroprotective agents to mitigate the effects of Pb-induced neurotoxicity remains vague. Objectives: This study aimed at investigating the neuroprotective effects of pre-treatment with vitexin and C. cajan extract against Pb-induced neurotoxicity in Wistar rats. Methods: Twenty-four male Wistar rats were randomly assigned into four groups (n=6). The control group was administered 0.5 mL of distilled water, Pb group received Pb acetate (200 mg/kg), vitexin+Pb group received Vitexin (50 mg/kg) an hour before Pb acetate (200 mg/kg), and C. cajan+Pb group received C. cajan (50 mg/kg) an hour before Pb acetate (200 mg/kg). All treatments were done within 28 days. Barnes maze test and novel object recognition (NOR) test were done to ascertain working memory, while the levels of oxidative stress markers (MDA, SOD, and GPx) were also tested. In addition, prefrontal cortical sections were stained with H&E stain, and the immunoreactivity of Iba1 and Nrf2 was examined. Results: There was a significant decline in working memory in the Pb group, but good working memory was maintained in vitexin and C. cajan pretreated groups. In vitexin and C. cajan pretreated groups, oxidative stress, neuronal damage, and expression of Iba1 were significantly low compared to the Pb group. Also, Nrf2 expression in the Pb group was significantly low compared to other groups. Conclusion: Pretreatment with vitexin and C. cajan offers neuroprotection against Pb toxicity via antioxidant and anti-inflammation actions. Although both vitexin and C. cajan extract showed neuroprotective abilities, vitexin exhibited better results.